2011
DOI: 10.1007/s10533-011-9659-y
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of plant derived organic matter in soil, loess and rhizoliths based on n-alkane molecular proxies

Abstract: Organic matter (OM) in loess-paleosol sequences is used for paleoenvironmental reconstructions, based e.g. on stable carbon isotope composition. Loess OM (LOM) is assumed to derive from synsedimentary vegetation, i.e. predominantly grass. However, low organic C contents make LOM prone to postsedimentary contamination. It was the aim of this study to reveal (1) whether OM of the loess sequence at Nussloch (SW Germany) was altered by postsedimentary input, (2) to which depth, and (3) from which source vegetation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 59 publications
2
21
1
Order By: Relevance
“…This result was of high importance, supporting the largely anecdotal evidence that shrub dominated the areas across the basin study area that is used to be dominated by grasses [Buffington and Herbel, 1965]. At the Los Piños sites, due to the similarities between grama grass and juniper n-alkane signatures, there was a degree of difficulty in determining between sources; based upon n-alkane signature, a problem was previously experienced when using n-alkane signatures alone [Marschner et al, 2008;Gocke et al, 2011]. However, the use of n-alkane signatures from piñon and combined with the δ 13 C values of both piñon and juniper demonstrated that the same trends transcend to the mountainous, grassland to piñon-juniper transition [Wilcox et al, 2003b].…”
Section: Change In the Source Of C Over Vegetation Transitionssupporting
confidence: 62%
“…This result was of high importance, supporting the largely anecdotal evidence that shrub dominated the areas across the basin study area that is used to be dominated by grasses [Buffington and Herbel, 1965]. At the Los Piños sites, due to the similarities between grama grass and juniper n-alkane signatures, there was a degree of difficulty in determining between sources; based upon n-alkane signature, a problem was previously experienced when using n-alkane signatures alone [Marschner et al, 2008;Gocke et al, 2011]. However, the use of n-alkane signatures from piñon and combined with the δ 13 C values of both piñon and juniper demonstrated that the same trends transcend to the mountainous, grassland to piñon-juniper transition [Wilcox et al, 2003b].…”
Section: Change In the Source Of C Over Vegetation Transitionssupporting
confidence: 62%
“…In addition, with respect to the degree to which wax lipid chain length patterns vary between the leaves and roots of plant species, there appears to be quite some variability. In general, the observed differences between roots and leaves of the same species are reported to be of the same order of magnitude as the differences between leaves of different species (e.g., Jansen et al, 2006;Kirkels et al, 2013;Gocke et al, 2014).…”
Section: Leaf Versus Root Inputmentioning
confidence: 85%
“…However, this may be different for the wax lipids, i.e., n-alkanes, n-alcohols, n-fatty acids, and isoprenoids, that have been found to occur in the leaves and roots of species at varying concentrations (Jansen et al, 2007;Huang et al, 2011). Particularly when such wax-derived lipids are applied as molecular proxies for vegetation cover in soil, root input can be an issue for two reasons: (i) roots may contain a different wax lipid composition than leaves qualitatively and quantitatively, thereby clouding the leaf signal Martelanc et al, 2007) and (ii) young root input at depth may disrupt the chronology of a reconstruction in time by overprinting the originally present signal Gocke et al, 2014).…”
Section: Leaf Versus Root Inputmentioning
confidence: 99%
“…Several studies reported long-chain n-alkanes not only in leaves but also in other plant parts (roots, stems, blossoms; e.g. Wöstmann, 2006;Jansen et al, 2006;Kirkels et al, 2013;Gocke et al, 2013), but in these studies the patterns show preferential synthesis of shorter chains (< n-C 25 ) with low OEPs, as well as much lower nalkane concentrations (3 to 10 times) than in leaves.…”
Section: Introductionmentioning
confidence: 96%